Education in South-East Asia - Symaco, Lorraine Pe 1978- (Education around the world series, 2013)
Education in South-East Asia is a comprehensive critical reference guide to education in South-East Asia. With chapters written by an international team of leading regional education experts, the book explores the education systems of Brunei Darussalam, Cambodia, Indonesia, the People's Democratic Republic of Lao, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste and Vietnam. The diverse range and forms of culture, religion and politics embedded in the region are exhibited in the distinctive education systems that inter-relate in one of the most integrated regions in the world. Including a comparative introduction to the issues facing education in the region as a whole this is an essential reference for researchers, scholars, international agencies and policy-makers at all levels.